MODERN TECHNOLOGIES FOR FAMILIARIZING PRESCHOOLERS WITH FICTION (Scientific journal of the Fergana State University, 2024)
This article shows that fiction is a tool that reveals human and spiritual values, serves as a powerful and effective tool for intellectual, moral and aesthetic education of children, has a great impact on the development and enrichment of children's speech, and preschool children. it is about modern technologies of introducing works of art.